Correction: Genome-Wide Reprogramming of Transcript Architecture by Temperature Specifies the Developmental States of the Human Pathogen Histoplasma. - Sarah A Gilmore; Mark Voorhies; Dana Gebhart; Anita Sil (PLoS Genetics, 2021)
[This corrects the article DOI: 10.1371/journal.pgen.1005395.].